Glycoproteins identified from heart failure and treatment models. Issue 2 (9th October 2014) - Yang, Shuang; Chen, Lijun; Sun, Shisheng; Shah, Punit; Yang, Weiming; Zhang, Bai; Zhang, Zhen; Chan, Daniel W.; Kass, David A.; van Eyk, Jennifer E.; Zhang, Hui; Pandey, Akhilesh; et al.
<x xml:space="preserve">Abstract</x> Conduction abnormalities can lead to dyssynchronous contraction, which significantly worsens morbidity and mortality of heart failure. Cardiac resynchronization therapy (CRT) can reverse ventricular remodeling and improve cardiac function. Although the underlying molecular changes are unknown, the use of a canine model of dyssynchronous heart failure (DHF) and CRT has shown that there are global changes across the cardiac proteome. This study determines changes in serum glycoprotein concentration from DHF and CRT compared to normal. We hypothesize that CRT invokes protective or advantageous pathways that can be reflected in the circulating proteome. Two prong discovery approaches were carried out on pooled normal, DHF, and CRT samples composed of individual canine serum to determine the overall protein concentration and the N‐linked glycosites of circulating glycoproteins. The level of the glycoproteins was altered in DHF and CRT compared to control sera, with 63 glycopeptides substantially increased in DHF and/or CRT. Among the 32 elevated glycosite‐containing peptides in DHF, 13 glycopeptides were reverted to normal level after CRT therapy. We further verify the changes of glycopeptides using label‐free LC‐MS from individual canine serum. Circulating glycoproteins such as alpha‐fetoprotein, alpha‐2‐macroglobulin, galectin‐3‐binding protein, and collectin‐10 show association to failing heart and CRT treatment model.